Diario social di un Rettore La chimica nel paese di Facebook - Dei, Luigi (Libere carte, 2016)
Download the free epub version Listen to the interview on Radio Treccia Ischia TV Is it possible to disseminate science through social networks? Facebook was created to share thoughts, ideas, sensations and anything mild and fleeting; certainly not for the dissemination of scientific and academic knowledge. On the contrary... by combining the obligatory conciseness of a post, the taste for fantasy at the service of the dissemination of scientific knowledge, and the socialization of such a widespread means of communication, there is a metamorphosis turning the irreversible, ineffable volatility of a social network into the lapidary and realistic fixity of this book of digital cameos, dedicated to many aspects of chemistry, a science which is so inextricably enveloped in our daily life. A "chemical" Rector disguises himself as Alice and ventures into a land, the Facebook land, where the wonders coming from imaginative journeys in matter, in its laws and in its imponderable enigmatic nature, take shape.